Risk Mitigation Strategies in Jumbo Bagging Process Using Failure Mode and Effect Analysis and Fault Tree Analysis Methods : Strategi Mitigasi Risiko pada Proses Jumbo Bagging dengan Menggunakan Metode Failure Mode and Effect Analysis dan Fault Tree Analysis - Izhaq, Dhuha Cahya; Aryanny, Enny (Indonesian Journal of Innovation Studies, 2025)
General Background: In industrial packaging systems, risk mitigation is essential to ensure operational continuity and product quality. Specific Background: At PT XYZ, the jumbo bag packaging process has been hindered by critical failures such as inaccurate weighing and process disruptions. Knowledge Gap: Existing risk management practices lack integrated analysis tools that link failure prioritization with root cause identification. Aim: This study aims to develop an effective risk mitigation strategy using a combination of Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA). Results: The analysis identified high-risk factors, including sensor failures, equipment instability, and manual handling issues. The highest Risk Priority Numbers (RPNs) guided focus areas, while FTA traced these to their root causes. Novelty: The study proposes a comprehensive automation-based solution—Alternative 5—integrating a Hopper Translator, Loadcell Weighing System, Conveyor in Bag, Machine D modifications, and PLC control. Implications: Implementation of this strategy significantly enhanced accuracy, safety, efficiency, and worker satisfaction. These findings underscore the value of automation and preventive maintenance as a synergistic approach to reducing operational risk and optimizing industrial performance.  Highlights: Identifies root causes of failure using FMEA–FTA integration. Proposes automation as a key solution to high-risk issues. Enhances accuracy, safety, and efficiency in packaging. Keywords: Risk Mitigation, FMEA, FTA, Automation, Packaging Process